DETERMINATION OF TOTAL NITROGEN MATTER AND PROTEIN CHANGES DURING RIPENING OF BIENO CHEESE - Dimitrovska, Gordana; Srbinovska, Sonja; Joshevska, Elena; Makarijoski, Borche (International Journal of Research -GRANTHAALAYAH, 2021)
The main purpose of this research was to determine the dynamic of total nitrogen matter and protein changes during ripening period of three kinds of indigenous Bieno cheese (A, B and C) in the region of Mariovo. The three kinds of Bieno cheese were produced with different traditional technologies. The cheese samples were analyzed for total nitrogen matter and protein during ripening process in five time intervals (in curd, after ripening, after salting, at 20-th day, at 45th day). The concentration of total nitrogen matter in examined Bieno cheese samples was between 3.98±0.06% to 4.16±0.15% and the concentration of protein in examined Bieno cheese samples was between 25.48± 0.49% to 26.53±0.93%. No significant differences in total nitrogen matter and protein concentration for p<0.05 and p<0.01 were determined. Proteolysis is affected by the type and amount of enzyme, the temperature during the ripening of the cheese, the length of ripening and the activity of the enzymes. The technological process of production, in essence, greatly affects the dynamics and breakdown of proteins, which is confirmed by our research.